PERAN DOA DAN IBADAH DALAM MENGUATKAN PROSES BELAJAR - Nuro Azlina Puadi; Sarwadi Sulisno (CV. ADIBA AISHA AMIRA, 2025)
This study explores the role of prayer and worship in strengthening students’ learning processes from the perspective of Islamic psychology and education. Employing a qualitative literature study, it examines classical sources such as the Qur’an and Hadith along with modern studies in psychology. Findings indicate that prayer enhances focus and inner peace, while worship builds discipline and emotional balance. Both act synergistically to develop students’ intrinsic motivation, self-control, and intellectual resilience. The study concludes that integrating spiritual elements like prayer and worship into education enhances the harmony between intellectual and spiritual development.